NILAI MORAL DALAM FABEL ANAK - Anggita Elma Vira; Eggy Fajar Andalas (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2022)
Fables become a medium of conveying moral values conveyed in the story. These values are helpful in the formation of children's character and can get used to having confidence in the value of kindness until the child grows up. Therefore, this study was conducted to study moral values in the fable. This research is qualitative research with an ethical approach. The data sources in the study were 18 fable stories taken from the page https://www.ebookanak.com/category/dongeng/kumpulan-dongeng-binatang-pilihan/. Eighteen of the fables are Gagak Ingin Jadi Angsa, Kaki yang Dibenci Rusa, Hadiah dari Burung Pipit, Tipu Daya Raja Biru, Harimau Bertopeng Rusa, Lolongan Si Guki Anjing, Suara Aneh dari Lapangan, Hewan Paling Beruntung, Jasa Lembu yang Terlupakan, Keberuntungan Katak Tuli, Mas Koki Tak Pernah Menyerah, Pulpen dan Kertas Ajaib Burung Merak, Hadiah Istimewa Serigala, Rubah Memperdaya Harimau, Tikus Penolong Gajah, Raja Bulan Penguasa Danau, and Kilauan Emas di Danau. The data in this study is a unit of story that contains the moral value of the fabled story. The data collection technique in this study uses a content analysis method, which looks for values contained in data in the form of fable text in electronic books. Data analysis techniques include data reduction, presentation, conclusion, and verification. From the research conducted, it can be concluded that of the eighteen fables, some moral values are conveyed implicitly, for example, from wrong actions shown by reply if someone commits moral deviations. Eight forms of moral values refer to the social relationship and relationship of beings with God, which include love for God and the environment, honesty, independence, respect and polite in the mind of language and behavior, confidence and hardworking, as well as generous and generous, kind and humble, and tolerant and harmonious.